Rapports aux savoirs et pratiques critiques en communauté de recherche philosophique : quels enjeux pour les élèves et les enseignants ? - Mathieu Gagnon (Éducation et Socialisation)
Supported by research data from studies conducted since 2008, this article examines the relation between, critical thinking and the relation students and teachers have to knowledge. It demonstrates notably, that the exercise of critical thinking appears to be linked to the relation to knowledge and varies according to the concepts and disciplines studied. The author then highlights the challenges with witch the students and teachers have to compose with when they engage in philosophical dialogue, considering that the knowledge that is discussed comes from varied disciplines and that the dynamics of teaching-learning within that context sometimes clashes profoundly with the traditional academic experience.